Kontribusi Modal Sosial dalam Kesuksesan Revitalisasi Permukiman Kumuh Kota Palembang - Damayanti, Alfina; izzudin, Muhammad; Yanti, Mery; Hapsari, Dyah (geoedusains: Jurnal Pendidikan Geografi, 2022)
Slum settlements are one of the problems in developing countries, including in Indonesia, one of which is in the city of Palembang. One way to reduce slum settlements is by revitalizing them. One of the revitalization of slum settlements carried out by the people of Palembang City is located in the 26 Ilir sub-district by turning the slum settlements into a clean and beautiful area which is carried out in mutual cooperation which is the social capital owned by the community. In simple terms, social capital can be understood as productive assets owned by each individual in a group or society that can be developed and utilized to achieve goals for mutual benefit. This research focuses on the social capital owned by the community in turning slum settlements into Kampung Sayur Cempako, Kelurahan 26 Ilir, Palembang City. This study uses a qualitative method with a descriptive approach. Methods of data collection consisted of observation, interviews with ten informants who were determined purposively, and documentation. The results of the study show that social capital in the form of mutual cooperation, norms, networks, trust, reciprocity, and proactive actions owned by the community can help the community overcome obstacles in revitalizing slum areas